RFID timing antenna for open water swimming competitions - Woellik, H. (Proceedings, 2018)
RFID timing is the common method for processing results in mass sport events. Typically, it is used in running, cycling and triathlon events, but with some modifications even swimming athletes in water can be detected. In open water swimming competitions, the distance between the athletes and the RFID antenna must be larger so that escort boats or small ships can pass the gate without getting into dangerous situations. In this paper a design of an underwater RFID antenna is presented which was used during swimming events, It could span a distance up to 12 m width inside a swimming channel or offshore. The whole construction was completely immerged under the water line. The electronic components were housed in some meter distance on the beach, in a boat or in a buoy. With a reading range up to 1.5 m distance a detection rate between 94.6% and 100% could be achieved.